Antimetastatic Effects of Curcumin in Oral and Gastrointestinal Cancers - Davoodvandi, Amirhossein; Farshadi, Marjan; Zare, Noushid; Akhlagh, Seyed Amirreza; Alipour Nosrani, Esmail; Mahjoubin-Tehran, Maryam; Kangari, Parisa; Sharafi, Seyedeh Maryam; Khan, Haroon; Aschner, Michael; Baniebrahimi, Ghazaleh; Mirzaei, Hamed (Frontiers in Pharmacology, 2021)
Gastrointestinal (GI) cancers are known as frequently occurred solid malignant tumors that can cause the high rate mortality in the world. Metastasis is a significant destructive feature of tumoral cells, which directly correlates with decreased prognosis and survival. Curcumin, which is found in turmeric, has been identified as a potent therapeutic natural bioactive compound (Curcuma longa). It has been traditionally applied for centuries to treat different diseases, and it has shown efficacy for its anti-cancer properties. Numerous studies have revealed that curcumin inhibits migration and metastasis of GI cancer cells by modulating various genes and proteins i.e., growth factors, inflammatory cytokines and their receptors, different types of enzymes, caspases, cell adhesion molecules, and cell cycle proteins. Herein, we summarized the anti-metastatic effects of curcumin in GI cancers, including pancreatic cancer, gastric cancer, colorectal cancer, oral cancer, and esophageal cancer.